THE EFFECT OF THE GOVERNMENT FINANCIAL INFORMATION MANAGEMENT SYSTEM (GFMIS) ON GOVERNMENT FINANCIAL PERFORMANCE IN IRAQ - Hussein Ali Hisab; Yasir Majeed Dahdooh; Dlawar Qader Abbas (Scholar Express Journals, 2024)
This research aimed to investigate the effect of the Government Financial Information Management System (GFMIS) on Government financial performance In Iraq. The research results demonstrated that GFMIS affected the Government's financial performance positively and significantly. The results also showed that there were no differences between the study samples with regard to the research variables represented in GFMIS and Government financial performance according to the demographic variables being studies
Keywords: government financial; management information system; financial Performance